Territorial governance in the context of RIS3 smart specialisation strategy - Jaime Del Castillo; Jonatan Paton; Belen Barroeta (European Regional Science Association (ERSA), 2014)
In the current new competitive environment, smart specialization has emerged strongly as a territorial development model to increase the efficiency and effectiveness of economic systems. An aspect from which it differs from previous models is the special emphasis on governance. In this framework, new RIS3 smart specialization strategies represent an opportunity to lay the foundations of a new governance to generate regional innovation systems that are more coordinated, efficient and effective. However, all this raises an important sophistication from the point of view of the system and the process. Thus, a smart specialisation governance requires considering a multidimensional scale of not only agents and relations, but also policies from different competence fields (e.g. innovation, education, employment, environment, etc.). The aim of this article is to analyse the concept of governance under the frame of the new competitive context that territories are facing, and more specifically towards the territorial development model of smart specialization, from the opportunity that its multidimensional approach can offer. This can be translated into the search for new policies and processes from the combination of the traditional ones in innovation, education, employment policies. In the first chapter, an overview of the major determinants of the current context is provided. In the second chapter, our definition of governance is presented referred to a regional innovation system, understood as a system of actors and relationships covering the different dimensions regional development must consider from a coordinated, efficient and effective way. In the third chapter, our definition of governance and its elements are taken to the field of smart specialization, and the implications for innovation systems and RIS3 strategic processes are discussed. The fourth chapter seeks to go beyond the theoretical definition of governance and presents a first set of issues to consider, difficulties and recommendations arising from the implementation on the territory. Finally, the article ends with some conclusions to be considered for those exercises that are currently being put in place to move towards a regional smart specialization and that require a more sophisticated governance that will give response to its theoretical and practical implications
Keywords: 330; P48 Political Economy; Legal Institutions; Property Rights; Natural Resources; Energy; Environment; Regional Studies